Constructed Wetland as an Endeavour to Protect the Environment: Study of Takhrij and Syarah Hadith - Iqrimatunnaya, Iqrimatunnaya; Hasannia, Ali (Journal of Takhrij Al-Hadith, 2022)
This study purpose to discuss the hadith about the Contrusted Wetland. This study uses a qualitative approach by applying the descriptive-analytical method. The formal object of this research is the science of hadith, while the material object is the hadith about the Construsted Wetland in the riwayah of Darimi No. 651. The results and discussion of this study indicate that the status of quality hadith hasan li ghairihi that meets the qualifications of maqbul ma'mul bih for practicing Islam. This study concludes that the Hadith of Darimi No. 651 is relevant to be used as inspiration for the development of the Construsted Wetland in the form of inclusive, human-centered technology.